Paul as an Early Witness to the Jewish Notion of Liberation-through-Torah - Ruzer, Sergʹ (Journal for the study of the New Testament, 2018)
This study focuses on Paul's 'liberation language' in Galatians, re-examining Shlomo Pines's suggestion that Paul responded to a tendency, attested in later rabbinic sources, to present the Torah as intrinsically linked to true liberty. The study first analyses the apostle's supposed polemical response, with the characteristic motif of the gift of the Spirit - instead of the Torah - as the guarantor of the eschatological freedom; its probable Jewish matrix is also outlined. Further, it is argued that side-by-side with Paul's Spirit-centered line of argument, a positive appraisal of the Torah-of-freedom concept can also be discerned in Galatians. The epistle thus becomes a witness for the early provenance of that broader Jewish tendency.